Noninvasive neuromonitoring in the operating room and its role in the prevention of delirium. Issue 2 (July 2021) - Zugni, Nicola; Guadrini, Lucrezia; Rasulo, Frank
Abstract : Delirium is a frequent and serious complication after surgery. It has a variable incidence between 20% and 40% with the highest incidence in elderly people undergoing major or cardiac surgery. The development of postoperative delirium (POD) is associated with increased hospital stay lengths, morbidity, the need for home care, and mortality. Studies have appeared in the last decade that evaluate the use of noninvasive monitoring to prevent its development. The evaluation of the depth of anesthesia with processed EEG allows to avoid awareness and burst suppression events. The cessation of brain activity is associated with the development of delirium. Another noninvasive monitoring technique is NIRS for cerebral tissue hypoxia detection by measuring regional oxygen saturation. The reduction of this parameter does not seem to be associated with the development of POD but with postoperative cognitive dysfunction. There are few studies in the literature and with conflicting results on the use of the pupillometer and transcranial Doppler in predicting the development of postoperative delirium.